2006
DOI: 10.1021/ja0573864
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Chain Walking Polymerization and Atom Transfer Radical Polymerization for Efficient Synthesis of Dendritic Nanoparticles for Bioconjugation

Abstract: A tandem chain walking polymerization (CWP) and ATRP was developed for efficient synthesis of nanoparticles for bioconjugation. Using the chain walking palladium-α-diimine catalyst (catalyst 1), dendritic polymers bearing multiple initiation sites were synthesized and used as macro-initiators for subsequent Cu(I)-mediated ATRP. Control of molecular weight and size of the water soluble core-shell polymeric nanoparticles was achieved by tuning reaction conditions. Addition of N-acryloyloxysuccinamide (NAS) monom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 20 publications
0
80
0
Order By: Relevance
“…Pd-diimine catalysts have been reported to be tolerant of the a-bromoester functionality. [14] The successful incorporation of BIEA into the copolymers through the enchainment of the acrylate group was confirmed by NMR elucidation of the copolymer structure. A representative 1 H NMR spectrum of PE-BIEA-1 is shown in Figure 1, along with those of the BIEA comonomer and the homopolyethylene, HomoPE, for comparison.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Pd-diimine catalysts have been reported to be tolerant of the a-bromoester functionality. [14] The successful incorporation of BIEA into the copolymers through the enchainment of the acrylate group was confirmed by NMR elucidation of the copolymer structure. A representative 1 H NMR spectrum of PE-BIEA-1 is shown in Figure 1, along with those of the BIEA comonomer and the homopolyethylene, HomoPE, for comparison.…”
Section: Resultsmentioning
confidence: 88%
“…[11,13] The combination of chain walking polymerization (CWP) with other polymerization techniques is needed in order to incorporate other types of comonomers at high percentages. Guan et al [14] showed an example by coupling the CWP technique with ATRP and synthesized hyperbranched polyethylenes tethered with ATRP initiating sites by copolymerizing of ethylene with functional alk-1-enes bearing a-bromoester sites using Pd-diimine catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Additionally, a tandem polymerization strategy combining chain walking polymerization and atom transfer radical polymerization (ATRP) was also developed to synthesize functionalized copolymers with core-shell structure. [8] In contrast to ethylene polymerization, homopolymerizations of linear a-olefins such as propylene, 1-hexene, and 1-octene catalyzed by a-diimine palladium catalysts generally lead to branched poly(a-olefin)s. [9] Comparing to linear a-olefins, branched a-olefins are scarcely reported as polymerization monomers with late transition metal complexes in the current literatures due to their enhanced steric bulk. One example is copolymerization of ethylene and 3,3-dimethyl-1-butene reported by Xiang and Ye with Pd-diimine catalyst, and 3,3-dimethyl-1-butene can be directly incorporated in the copolymer.…”
Section: Introductionmentioning
confidence: 99%
“…The same trends were observed in the other hyperbranched polymers and dendrimers. [23,24] (Insert Table 1 (Insert Figures 3 and 4 here) …”
Section: Synthesis Of Hyperbranched Phenolic Polymer (Hbp)mentioning
confidence: 99%